Neoantigens in cancer immunoediting: from mechanisms to personalized vaccines in breast cancer - Zeng, Shiyan; Wang, Li; Zeng, Wanqin; Sun, Lei (Frontiers in Cell and Developmental Biology, 2026)
Tumor neoantigens, a class of entirely novel antigens generated by somatic mutations, can be specifically recognized by T cells and serve as a central bridge connecting tumor genomic variation with anti-tumor immune responses. This review systematically elaborates on the dual role of neoantigens in the dynamic process of immunoediting: they act as targets for immune attack that are “sculpted” and as drivers of tumor evolution that are “selected.” It further explores their immense potential as targets for personalized immunotherapy. By delving into the mechanisms of neoantigen generation, identification strategies, and their pivotal role within the cancer-immunity cycle, the review focuses on the latest advances in neoantigen-based DNA, RNA, and synthetic peptide vaccines. Notably, drawing on a first-in-human clinical trial of a neoantigen DNA vaccine in triple-negative breast cancer (TNBC), it validates the safety, clinical feasibility, and potent immunogenicity of this therapeutic strategy. Finally, the article discusses how to address core challenges such as tumor heterogeneity and immune escape by integrating cutting-edge strategies including artificial intelligence prediction, rational multi-epitope design, and combination therapies. This provides a solid theoretical foundation and promising clinical translation prospects for personalized immunotherapy in breast cancer and other solid tumors.